Politik Hukum Pengawasan Profesi Notaris : Studi Komparatif Sistem Perlindungan Profesi di Indonesia dengan Negara Berkembang Lain - Rini Oktaviana (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
This study examines the evolution of the notary supervision system in Indonesia, particularly the impact of Constitutional Court Decision No. 49/PUU-X/2012 which revoked Article 66 paragraph (1) of Law No. 30 of 2004 and the establishment of the Notary Honorary Council (MKN) through Law No. 2 of 2014. The study uses a normative juridical method with a case and statutory approach, supported by literature analysis and expert opinion. The results show that the Constitutional Court decision eliminated legal protection for notaries in facing arbitrary actions by law enforcement officers, creating inequality with other professions such as advocates and doctors. Although the Regional Supervisory Council (MPD) still exists institutionally, the authority to grant approval for summoning notaries has been lost. In response, the government established the MKN which combines elements of the Ministry of Law and Human Rights with the Indonesian Notaries Association. International comparisons show that the civil law system provides stronger protection through specialized courts, while common law does not provide a privileged position for notaries. Indonesia adopts a mixed model that provides flexibility but creates coordination complexity. The MKN plays a role in enforcing professional ethics while maintaining a balance between the protection of notaries as public officials who make authentic deeds and accountability in the judicial system, restoring the stability of legal protection that was lost after the Constitutional Court's decision.